العقل الجاهلي كما يصوره القرآن الكريم :b - شاكر، إيمان حكمت (Kulliyyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, International Islamic University Malaysia, 2008)
The research in mainly concerned with pre-Islamic thought and mind with reference to theology, especially as documented in the Quran. The study details six aspects of theology in the Jahili mind; the law of polytheism or multiple gods, polytheism, blind imitation, inconsistencies, fallacies, and the Jahili concept of God. A major problem that the study addresses is the concept of Jahiliyyah; is it an objective intellectual state or a historical period? The study also examines the way in which the Quran portrayed Jahiliyyah in order to confront it. The researcher employed a comprehensive inductive approach to study Jahiliyyah, Jahili mind and all that is related to them in the Quranic text, the emplayed an analytical approach to examine all these texts. The study concluded that the Quranic texts question and attack the Jahili mind for its ignorance and regidity. As for Jahiliyyah itself, the study concludes that it is predominantly an objective intellectual state that affects all societies in different degrees.